SINERGISITAS KEBIJAKAN DAN STRATEGI PENCEGAHAN TINDAK PIDANA TERORISME DI PROVINSI BALI - Putra, I Made Walesa; Dike Widhiyaastuti, I Gst Agung Ayu (VYAVAHARA DUTA, 2018)
The Writing of â€œThe Synergicities of Policies and Strategies of PreventionÂ  Terrorismâ€™s Crime of Bali Provinceâ€ are aimed to develop legal science in general and particular in the field of criminalâ€™s law as well as knowing and studying the synergy between roles and strategies from the government, law enforcers and the community and to find, to analyze, to review and to provide legal solutions to obstacles in the effort to prevent terrorism in crime of Bali Province so it can be constructed to be an effective counter measures formulation. The method used in the achievement of the goal is approach Juridical Empirical method, namely legal research with facts approach by observation and in-depth interviews on object of research. The research was conducted on Bali Police, Kesbangpolinmas Bali, FKPT, FKUB, MUDP, and Religious figures in Bali. The results disclosed that each agency / organization / institution / individual has carried out the obligations according their tasks effectively and strive synergize the policies and strategies of prevention in terrorism. There are a few obstacles ranging from funding, facilities, quality-quantity of human resources to the constraints associated with legislation. By identifying several issues and to find the best solution for more effective prevention of acts of terrorism in synergy and sustainable.